Stability of the North Spur at Muskrat Falls : Comments and Discussion of a Paper by Stig Bernander and Lennart Elfgren - Bernander, Stig; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och brand, 2021)
In Part A, the geotechnical background is presented to a stability problem regarding the North Spur dam wall at Muskrat Falls in Churchill River in Newfoundland, Canada. This land was formed in the regression of the sea during and after the last ice age with deposits of multiple layers of silty sands and silty sandy clays that formed the valleys and plains that are now above sea level. Some of these layers, deposited thousands of years ago in post-glacial times, are vulnerable to liquefaction when they are disturbed. These conditions have in the past repeatedly caused slides along the banks of the Churchill river. In the report, a specific type of possible progressive failure –the most dangerous one in respect of the safety of the North Spur – is discussed. This type of landslide development may be caused by the rising water pressure, when - or after - the dam is impounded. As will be explained, such a slide could force part of the North Spur ridge to slide along a failure surface sloping East-wards into the deep river whirlpool downstream of Muskrat Falls. In the following, a brief overview is provided of the geotechnical background behind our concerns, also discussing methods of mitigating the risk of the kind of slopefailure in question. Hence, we propose measures such as compacting the soil by piling or by methods of grouting and drainage. We also suggest the need for an expert Advisory Panel to look further into the long-term safety of the North Spur. In Part B, the paper in Part A is discussed and the risk for a failure is denied. In Part C, finally, the authors of Part A, give their answer to the criticism and uphold their view: There may be a serieois risk for a dam breach caused by weak soil layers in the dam. This risk should be properly investigated and mitigated.